2009
DOI: 10.1177/1468794109343625
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the standard interview: the use of graphic elicitation and arts-based methods

Abstract: This article reviews three visual methods based on drawing that I applied in my research on young people: the arts-based projective technique, the self-portrait, and the graphic elicitation methods of the relational map and the timeline. Examples of these methods are drawn from their application in two studies, the Narratives of Identity and Migration project, exploring young people and identities in England and Italy, and the Young Lives and Times. The article argues that applying these drawing methods in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
521
1
47

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(577 citation statements)
references
References 18 publications
(15 reference statements)
8
521
1
47
Order By: Relevance
“…It seems likely that, as well as providing an engaging and nonthreatening means of communication about a difficult topic, the medium of the 'visual interview' also facilitated insightful exploration of that topic. Visual methods are sometimes considered superior to verbal research because they encourage expression of emotions when these may be difficult to articulate [40,41,60]. We found that the visual and verbal methods constantly strengthened each other, as other authors have highlighted [29,37,45].…”
Section: Using Visual Methodsmentioning
confidence: 47%
See 2 more Smart Citations
“…It seems likely that, as well as providing an engaging and nonthreatening means of communication about a difficult topic, the medium of the 'visual interview' also facilitated insightful exploration of that topic. Visual methods are sometimes considered superior to verbal research because they encourage expression of emotions when these may be difficult to articulate [40,41,60]. We found that the visual and verbal methods constantly strengthened each other, as other authors have highlighted [29,37,45].…”
Section: Using Visual Methodsmentioning
confidence: 47%
“…The transcript and image analyses were combined, and codes of meaning were grouped into emergent themes. These were sometimes derived directly from the drawings and their metaphors (see [40]). Once this was completed for each transcript, emergent themes were then clustered into superordinate and subordinate themes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The living graphs were then used alongside discussion and exploration in the interviews. Visual methodologies are a rapidly developing area of social enquiry (as in Bagnoli, 2009), but photos or artefacts are used more frequently to stimulate discussion (e.g. Cremin et al, 2011).…”
Section: Methodology and Theoretical Frameworkmentioning
confidence: 99%
“…This participative basis of visual research is also 8 highlighted by Packard (2008), who considers this type of method to contribute to empowering participants by creating more ethical research contexts and realities and generating new forms of knowledge that cannot be drawn out any other way. (Bagnoli, 2009;Harper, 2002;Keats, 2009;Pink, 2006;Prosser & Loxley, 2008) and even in researching identity positions that are usually silent (Croghan, Griffin, Hunter & Phoenix, 2008).…”
Section: Inclusive Research and Visual Methodsmentioning
confidence: 99%